2014
DOI: 10.1016/j.eujim.2014.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Moxibustion for treating rheumatoid arthritis: A systematic review and meta-analysis of randomized controlled trials

Abstract: Introduction: Moxibustion is widely used in China and other East Asian countries to manage the symptom of rheumatoid arthritis (RA) and to lessen the adverse effects of western medicine. The purpose of this systematic review was to evaluate the available evidence from randomized controlled trials (RCTs) of moxibustion for treating patients with rheumatoid arthritis (RA). Methods: Seven Chinese and English databases were searched to November 2013 from their inception. Eligible RCTs were included if moxibustion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 43 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…[4,5] Previous systematic reviews of moxibustion for RA have shown that moxibustion might be beneficial to RA patients. [6,7] One [6] of these studies included 8 randomized clinical trials (RCTs) in which moxibustion was compared with drug therapy in RA patients, and suggested that moxibustion might be beneficial. The second review [7] also described some favorable effects of moxibustion in the treatment for RA.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Previous systematic reviews of moxibustion for RA have shown that moxibustion might be beneficial to RA patients. [6,7] One [6] of these studies included 8 randomized clinical trials (RCTs) in which moxibustion was compared with drug therapy in RA patients, and suggested that moxibustion might be beneficial. The second review [7] also described some favorable effects of moxibustion in the treatment for RA.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several types of sham interventions suggested until now. It is one of the most commonly used types of sham interventions to apply acupuncture needles with a blunt edge and insulated moxibustion at nonacupoints [1618, 31, 4648]. No one can say for sure that it is a perfect and faultless method as a sham intervention for acupuncture and moxibustion study.…”
Section: Discussionmentioning
confidence: 99%
“…No one can say for sure that it is a perfect and faultless method as a sham intervention for acupuncture and moxibustion study. However, to date it is one of the best options that we can choose [4850]. …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, due to the number of RCTs in this research, we could not set subgroup analysis to minimize heterogeneity. In a previously published article [35], in order to solve the same problem, the author, who is an expert in evidence-based complementary and alternative medicine, also used the same method that we tried. In the future we will add enough trials to set subgroup analysis to solve this problem.…”
Section: Discussionmentioning
confidence: 99%